Nilai-Nilai Politik Pancasila Dalam Politik Kolaborasi Berbasis Kearifan Lokal (Studi Kasus Tradisi Sesaji Rewanda Goa Kreo Kota Semarang) (Jurnal Sosial Humaniora dan Pendidikan, 2026)
The ethical values of Pancasila are implemented in the tradition and local wisdom of "Sesaji Rewanda," which is organized by the community of Talun Kacang Hamlet, Kandri Subdistrict, Gunungpati District, Semarang City. This tradition and local wisdom are practiced and preserved by the community with the aim of maintaining the sustainability and harmony with the surrounding nature, especially by nurturing and sustaining the harmony of vertical relationships, between humans and God as well as horizontal relationships between humans and others, and the relationship between humans and nature, including animals and plants. The implementation of the "Sesaji Rewanda" tradition is filled with the ethical values of Pancasila, where rituals are carried out with meaningful symbolism. In this tradition, there are four ceremonial "gunungan" (mountain-shaped offerings of food) of rice carried by participants to the Jati Barang Reservoir. The offerings include "nasi golong" or what the locals call sego kethek (monkey rice), which may only be served with vegetables, tempeh, and tofu; a "fruit gunungan" as a symbol of harmony with animals and nature; a "lepet gunungan" (traditional sticky rice snack) symbolizing harmony among fellow human beings; and the main "gunungan of agricultural produce" representing harmony with the Creator, the Causa Prima. There are also gunungan of lepet and ketupat (rice cake). These four gunungan, each 2.5 meters tall, are part of the vibrant ritual of Sesaji Rewanda celebrated in the Kandri tourism village every 7th of Syawal. This local wisdom serves as an expression of gratitude to God Almighty for the blessing of nature and the ancestral legacy, passed down orally and through traditions from the community around Goa Kreo. It brings prosperity and welfare to agriculture and the lives of the people in Talun Kacang Hamlet, Kandri Subdistrict, Gunungpati District, Semarang City. The tradition of "Sesaji Rewanda," the development of the Jati Barang Reservoir, and the arrangement of the Goa Kreo tourist site exemplify a model of Collaborative Politics based on local wisdom, infused with the ethical-political values of Pancasila, and representing a form of collaborative politics among national political actors down to the local elite level.